2001
DOI: 10.1080/10578310127606
|View full text |Cite
|
Sign up to set email alerts
|

Immune Function in Adolescent Tennis Athletes and Controls

Abstract: Resting immune function and infection incidence were compared between 20 (10 male, 10 female) elite teenage tennis athletes and 18 (9 male, 9 female) non-athletic, age-matched controls. Male and female athletes trained an average of 17.6 ± 0.8 hours per week and possessed VO2max values that were 15% and 22% higher, respectively, than controls. NK cell counts were 53% higher (p = 0.015) and neutrophil counts were 16% lower (p = 0.030) in the athletes; however, salivary IgA output, serum/plasma concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Studies regarding inflammatory cytokines in regular exercisers bring varying results. Henson et al [ 25 ] found no significant difference between adolescent tennis players and controls in terms of serum/plasma IL-1RA and respiratory infections over 2.5 months. During the training season, no significant modifications in lymphocyte counts but a significant decrease in intracellular IL-2 and IL-4 production was described in Italian footballers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding inflammatory cytokines in regular exercisers bring varying results. Henson et al [ 25 ] found no significant difference between adolescent tennis players and controls in terms of serum/plasma IL-1RA and respiratory infections over 2.5 months. During the training season, no significant modifications in lymphocyte counts but a significant decrease in intracellular IL-2 and IL-4 production was described in Italian footballers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Henson et al have report no significant difference between adolescent tennis players and non-athletic controls in terms of serum/plasma IL-1ra and respiratory infections over 2.5 months. 20 During training season, a significant decrease in intracellular IL-2 and IL-4 production has been described in Italian footballers, 21 while lower plasma IL-1β, IL-18, IFNγ, and IL-1ra levels have been noted in Portuguese kayakers during the off-training season as compared to training season; this suggests that regular intensive exercise may have a beneficial anti-inflammatory effect. 22 In addition, significantly higher resting serum levels of periostin were noted in nine elite swimmers compared to ten asthmatic non-athletes and seven healthy subjects.…”
Section: Exercise and Systemic Inflammationmentioning
confidence: 96%
“…Studies on systemic inflammatory cytokines in regular exercisers report varying findings. Henson et al have report no significant difference between adolescent tennis players and non‐athletic controls in terms of serum/plasma IL‐1ra and respiratory infections over 2.5 months 20 . During training season, a significant decrease in intracellular IL‐2 and IL‐4 production has been described in Italian footballers, 21 while lower plasma IL‐1β, IL‐18, IFN‐γ, and IL‐1ra levels have been noted in Portuguese kayakers during the off‐training season as compared to training season; this suggests that regular intensive exercise may have a beneficial anti‐inflammatory effect 22 .…”
Section: Infection‐like Syndromes In Athletes—when No Pathogen Can Be...mentioning
confidence: 99%
“…With runners, sickness rates following a competitive marathon race have been observed to be highest in those exhibiting the lowest salivary IgA levels (Nieman et al, 2001). In two other studies, however, variance in salivary IgA concentration was not related to a history of URTI incidence in elite female rowers or adolescent tennis athletes (Henson et al, 2000;Nehlsen-Cannarella et al, 2000). Thus the data are inconclusive, and research is needed with larger groups of athletes followed for longer periods of time to determine the usefulness of salivary IgA concentration in predicting URTI risk in athletes.…”
Section: Resting Immune Function In Athletes and Nonathletesmentioning
confidence: 87%